Tough and competent: an autoethnography of secondary school redesign in Kansas - Scott, Jay (Kansas State University, 2023)
Beginning with the 2017-2018 school year, the Kansas State Department of Education implemented the Kansans Can School Redesign project (Redesign, hereafter) with the aim of fundamentally changing teaching and learning. The project was borne out of the feedback Kansans from across the state provided about what they believed education should be for current and future preK-12 students. The purpose of this qualitative study was to make meaning, from my lens as a coach, of secondary school leader experiences as they led their school through the Redesign process. This qualitative research study is an autoethnography where the researcher observes the interactions of key players and then, from the researcher’s perspective, shares the resulting impact on the culture by blending storytelling with research literature. Qualitative data was collected from field notes and observations of the school leadership team meetings and interviews with building principals. Through an analysis, the degree to which the school Redesign team balanced two leadership skills, acting as change agents and providing order to the change process, had a major impact on the culture within the school. Focusing too much on challenging the status quo with little consideration for structure and order, or vice versa, resulted in a lack of trust and ownership of the results of the Redesign process by the adults (teachers and community) and students. Those school Redesign teams that skillfully balanced disrupting the traditional environment of school while also providing order through predictable routines and protocols, were able to increase trust and ownership by the adults and students in the school.
Keywords: Kansans Can School Redesign Project; Redesign; School redesign team; Change agent; Order